2017
DOI: 10.1016/j.lfs.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone improves insulin sensitivity and reduces weight loss in Walker-256 tumor-bearing rats

Abstract: PGZ and PGZ+INS improved INS peripheral sensitivity, possibly by decreasing blood free fatty acids, and reduced fat tissue wasting and body weight loss in small tumor-bearing rats. The results suggest clinical benefits of PGZ in preventing INS resistance, adipose tissue wasting and weight loss when the tumor is small, i.e., in less severe cachexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 47 publications
5
20
0
Order By: Relevance
“…The W256 tumor‐bearing rat model has been previously used to study cancer‐induced cachexia. Cachexia was characterized by weight loss after tumor cell inoculation . Our results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…The W256 tumor‐bearing rat model has been previously used to study cancer‐induced cachexia. Cachexia was characterized by weight loss after tumor cell inoculation . Our results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the glucose produced by gluconeogenesis from glutamine and alanine must have been used as an energy source (anaerobic glycolysis) by the tumor. 45 As evidenced by the lower KITT (Figure 2), tumorbearing rats showed INS peripheral resistance, already observed in our studies, 5 which was not attenuated by any of the treatments. INS resistance in cancer has been associated with increased TNF-α, IL6, and FFA.…”
Section: Discussionsupporting
confidence: 75%
“…2 Lipolytic and proteolytic factors, such as lipid mobilizing factor (LMF), proteolysis-inducing factor (PIF), and proinflammatory cytokines (TNF-α, IL1, and IL6), play a central role in the development of metabolic alterations of cachexia. 1,2,4 However, hypoinsulinemia and insulin (INS) resistance, often present in cancer-bearing, [5][6][7][8][9][10] also appear to contribute to the metabolic changes of cachexia, since INS exerts important anabolic and anticatabolic effects in the metabolism of lipids, proteins and carbohydrates. Hypoinsulinemia related to cancer is caused by decreased secretion of INS by β-cells, 5,6,11 while INS resistance is attributed to the increase of cytokines (TNF-α and IL6) and free fatty acids (FFA) resulting from intense lipolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The W256 tumor-bearing rat model has been previously used to study cancer-induced cachexia. Cachexia was characterized by weight loss after tumor cell inoculation [109,110] . This study also demonstrated results consistent with previous studies ( Fig.…”
Section: Functional Analysis Of Differential Proteinsmentioning
confidence: 99%